Choice of Scheme for Classification - Ranganathan, S. R. (Journal of Information and Knowledge, 1968)
Rasamuls Molgaard-Hansen’s paper UDC, DC, and LC in competition on the domain of the university library has been the stimulus. (See also Sec 96 for comments on Perrault’s paper). After the definition of essential terms, CC, DC, LC, and UDC are compared in respect off the following points: 1 Faith in one scheme for shelf arrangement © books and for documentation lists; 2 Sequence of the main subjects according to the consensus of scholars and scientists; 3 Sequence of compound subjects; 4 Extent of facetisattuorn; 5 Verbal, idea, and notational planes; 6 Use of crisp words in schedules, so as to be fit for use in subject headings; 7 Guiding principles for the idea plane; 8 Obligation of notational plane to implement the findings in the idea plane; 9 Fault of “Starvation System.” ; 10 Versatility of the notational system; 11 Fault of alternative places for a subject; 12 Uniqueness of class number, assuming help from the catalogue and administration to meet the needs of minorities; 13 Value of freely faceted classification guided by principles; 14 Helpful places for newly emerging subjects; 15 Systematic procedure for classification; and 16 Organisation for future development.